Trial Watch: Immunotherapy plus radiation therapy for oncological indications - Vacchelli, Erika; Bloy, Norma; Aranda, Fernando; Buqué, Aitziber; Cremer, Isabelle; Demaria, Sandra; Eggermont, Alexander; Formenti, Silvia Chiara; Fridman, Wolf Hervé; Fucikova, Jitka; Galon, Jérôme; Spisek, Radek; et al. (Oncoimmunology, 2016)
Malignant cells succumbing to some forms of radiation therapy are particularly immunogenic and hence can initiate a therapeutically relevant adaptive immune response. This reflects the intrinsic antigenicity of malignant cells (which often synthesize a high number of potentially reactive neo-antigens) coupled with the ability of radiation therapy to boost the adjuvanticity of cell death as it stimulates the release of endogenous adjuvants from dying cells. Thus, radiation therapy has been intensively investigated for its capacity to improve the therapeutic profile of several anticancer immunotherapies, including (but not limited to) checkpoint blockers, anticancer vaccines, oncolytic viruses, Toll-like receptor (TLR) agonists, cytokines, and several small molecules with immunostimulatory effects. Here, we summarize recent preclinical and clinical advances in this field of investigation.
Keywords: ipilimumab; TGFβ1; Danger-associated molecular patterns; nivolumab; immunogenic cell death; pembrolizumab